2013
DOI: 10.1007/s00192-013-2162-3
|View full text |Cite
|
Sign up to set email alerts
|

Mesh pullout force: comparative study of different deployment techniques in a sheep model

Abstract: The EndoFast Reliant system provides significantly stronger attachment in the immediate postoperative period (0-3 days) compared with trocar-based techniques, and this difference disappeared at day 15 postsurgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Collagen I, II and inflammatory infiltrate levels were analysed at implant site 7, 30 and 90 Coating PP mesh with platelet-rich plasma enhanced tissue regeneration with higher total collagen concentration Promising results; however, it is unclear if these histology outcomes will result in better clinical outcomes Brazil Avila et al [ 34 ] Mesh B: mesh A coated with platelet-rich plasma extracted from blood via centrifuge Rabbit Mesh A: PP mesh Abdominal wall Meshes C and D were compared as alternative materials to commercially available Meshes A and B. Implants were placed in full-thickness abdominal wall defects 30 and 90 Meshes C and D had better outcomes, with decreased inflammatory response Promising results regarding alternative materials; however, these would need replication in larger animal models Belgium and UK Sabiniano et al [ 35 ] Mesh B: PVDF mesh Mesh C: polyurethane mesh Mesh D: poly-L-lactic acid Sheep EndoFast Reliant™ System Thigh fascia EndoFast Reliant™ System was used to insert mesh into sheep thigh fascia. Pullout force was measured at each endpoint 0, 3, 7, 15, 30 and 45 Test to investigate the strength of attachment; results showed that the experimental system provided much stronger mesh attachment than trocar-based methods Sheep thigh was used as the site of implantation owing to histological similarity, rather than vagina tissue Israel Alcalay et al [ 36 ] Only papers written in English language were included in the table eMSCs endometrial mesenchymal stem cells, ME mesh exposure, NHP non-human primate, NZW New Zealand White, PCL poly ε-caprolactone, PCU polycarbonate urethane, PDMS polydimethylsiloxane, POP pelvic organ prolapse, PP polypropylene, PVDF polyvinylidene fluoride, SD Sprague–Dawley …”
Section: Resultsmentioning
confidence: 99%
“…Collagen I, II and inflammatory infiltrate levels were analysed at implant site 7, 30 and 90 Coating PP mesh with platelet-rich plasma enhanced tissue regeneration with higher total collagen concentration Promising results; however, it is unclear if these histology outcomes will result in better clinical outcomes Brazil Avila et al [ 34 ] Mesh B: mesh A coated with platelet-rich plasma extracted from blood via centrifuge Rabbit Mesh A: PP mesh Abdominal wall Meshes C and D were compared as alternative materials to commercially available Meshes A and B. Implants were placed in full-thickness abdominal wall defects 30 and 90 Meshes C and D had better outcomes, with decreased inflammatory response Promising results regarding alternative materials; however, these would need replication in larger animal models Belgium and UK Sabiniano et al [ 35 ] Mesh B: PVDF mesh Mesh C: polyurethane mesh Mesh D: poly-L-lactic acid Sheep EndoFast Reliant™ System Thigh fascia EndoFast Reliant™ System was used to insert mesh into sheep thigh fascia. Pullout force was measured at each endpoint 0, 3, 7, 15, 30 and 45 Test to investigate the strength of attachment; results showed that the experimental system provided much stronger mesh attachment than trocar-based methods Sheep thigh was used as the site of implantation owing to histological similarity, rather than vagina tissue Israel Alcalay et al [ 36 ] Only papers written in English language were included in the table eMSCs endometrial mesenchymal stem cells, ME mesh exposure, NHP non-human primate, NZW New Zealand White, PCL poly ε-caprolactone, PCU polycarbonate urethane, PDMS polydimethylsiloxane, POP pelvic organ prolapse, PP polypropylene, PVDF polyvinylidene fluoride, SD Sprague–Dawley …”
Section: Resultsmentioning
confidence: 99%
“…Briefly, the 3 mm thick needle passer funneled through the abdominal wall tissue forces the 2 cm wide strap to roll along the axis. This principle of physics, already recognized in the literature, appears to be an appropriate way to ensure a fixation-free, but firm placement, of the polypropylene bands used for the treatment of female genital prolapse [ 25 , 26 , 27 , 28 , 29 ]. Therefore, the friction of the rolled strap surface in the narrow passageway allows for a stable placement amid the tissues crossed.…”
Section: Discussionmentioning
confidence: 99%